2014
DOI: 10.1002/jor.22683
|View full text |Cite
|
Sign up to set email alerts
|

Changes of density distribution of the subchondral bone plate after supramalleolar osteotomy for valgus ankle osteoarthritis

Abstract: CT-osteoabsorptiometry (CT-OAM) has been used to visualize subchondral bone plate density distribution regarding to its mineralization. The purpose of this study was to display and analyze the density distribution of the subchondral bone plate before and after supramalleolar realignment osteotomies. We retrospectively analysed pre-and postoperative CT images of nine consecutive patients with post-traumatic unilateral valgus ankle OA. The distribution charts of CT-OAM scans were quantitatively analyzed for subc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
6
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 36 publications
0
6
0
Order By: Relevance
“…Longitudinal radiographic studies have revealed a strong correlation between osteosclerosis and joint space narrowing, another major clinical sign of OA . Osteosclerosis of the subchondral bone is a reversible process in humans, as convincingly demonstrated by a decrease in subchondral bone mineral density in advanced post‐traumatic ankle OA after surgical joint distraction or osteotomy . While obviously strongly influenced by biomechanical factors, bone remodeling is a biological process involving osteoblasts, osteocytes, osteoclasts, blood capillaries, and various bone marrow resident cells such as macrophages and mesenchymal stem cells …”
mentioning
confidence: 99%
“…Longitudinal radiographic studies have revealed a strong correlation between osteosclerosis and joint space narrowing, another major clinical sign of OA . Osteosclerosis of the subchondral bone is a reversible process in humans, as convincingly demonstrated by a decrease in subchondral bone mineral density in advanced post‐traumatic ankle OA after surgical joint distraction or osteotomy . While obviously strongly influenced by biomechanical factors, bone remodeling is a biological process involving osteoblasts, osteocytes, osteoclasts, blood capillaries, and various bone marrow resident cells such as macrophages and mesenchymal stem cells …”
mentioning
confidence: 99%
“…The HU is recognized as CT numbers that correspond with the average amount of radiation absorbed by the tissues, and several reports demonstrated the usefulness of measurement of HU values to evaluate the stress distribution in several joints. 2,6,9,26,31 The HU is defined based on a scale created by the linear transformation of the original linear attenuation coefficient measurement into one where the radiodensity of distilled water at standard temperature and pressure is set at 0 and that of air at −1000. 3,18 The HU in several tissues can be derived.…”
Section: Introductionmentioning
confidence: 99%
“…5 The pivotal role of the subchondral bone in the diagnosis and treatment of OA has been shown following joint distraction arthroplasty 21 and corrective supramalleolar osteotomies, which resulted in decreased subchondral osteosclerosis and cysts following surgery. 9,26 Current routine diagnostic imaging for the diagnosis of OA includes conventional weight-bearing radiographs, which can be used to quantitatively measure the degree of joint space narrowing and subchondral osteosclerosis. 18,30,34 For a more detailed analysis, the single-photon emission computed tomography/computed tomography (SPECT-CT) may be used.…”
Section: Introductionmentioning
confidence: 99%